2010
DOI: 10.4028/www.scientific.net/amr.97-101.1578
|View full text |Cite
|
Sign up to set email alerts
|

Vibration Suppression of Flexible Beams Using MR Elastomers

Abstract: Magnetorheological (MR) elastomers are smart materials whose physical properties can undergo instantaneous and reversible change when subjected to different intensities of the magnetic field. This makes the MR elastomers have wide applications in the fields of vibration control. This work presents the vibration suppression of flexible beams with MR elastomers. An experiment system has been set up to investigate the vibration performances of a sandwich beam filled with MR elastomers. The vibration response of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…They reported 30% greater vibration reduction of an MRE-embedded cantilever sandwich beam in comparison to that of a sandwich beam with a viscoelastic material core. Wei et al (2010) experimentally evaluated the vibration response performance of the MR elastomer beam. The results demonstrated that the MR elastomer can shift the natural frequencies and reduce the vibration amplitude by applying the magnetic field.…”
Section: Introductionmentioning
confidence: 99%
“…They reported 30% greater vibration reduction of an MRE-embedded cantilever sandwich beam in comparison to that of a sandwich beam with a viscoelastic material core. Wei et al (2010) experimentally evaluated the vibration response performance of the MR elastomer beam. The results demonstrated that the MR elastomer can shift the natural frequencies and reduce the vibration amplitude by applying the magnetic field.…”
Section: Introductionmentioning
confidence: 99%
“…Through detailed studies, the effects of magnetic fields, core thickness, percentage of iron particles, and carbon blacks on the free vibration response and the region of parametric instability were studied for various boundary conditions. An experimental system was set up by Wei et al (2010) in order to investigate the vibration performances of a sandwich beam filled with MRE core. The results indicated that the MRE can shift the natural frequencies and decrease the vibration amplitudes when the magnetic field is employed.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the works concerned the subject of adaptive features of single segment beam structures incorporating MR fluid between two elastic layers [4,5,6,7]. Other works focused on the subject of incorporating magnetorheological elastomer into the middle layer [8,9]. The dynamic equations of sandwich beams were derived in [10,4] based on the Hamilton principle, by assuming the mode function of simply supported beam as a harmonic function, finally the modal frequency and loss factor of the beam were found out.…”
Section: Introductionmentioning
confidence: 99%